2007
DOI: 10.1097/psy.0b013e31814b8c0f
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Predicts Mortality and Morbidity After Coronary Artery and Valve Surgery—A 4-Year Follow-Up Study

Abstract: The results of the present study suggest that the assessment of psychosocial factors, particularly the ongoing assessment of anxiety, could help in risk stratification and identification of patients at risk of mortality and cardiovascular morbidity after cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
3
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(153 citation statements)
references
References 38 publications
7
138
3
5
Order By: Relevance
“…These scores are higher compared to the 29% in the study of Jiang [31] and lower compared to the 45% in the study of Friedmann [10]. In a study on patients after coronary artery or valve surgery, Szekely [12] found that 42% of these patients presented clinically significant anxiety symptoms. These results stress the importance to screen for anxiety as well as for depression.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These scores are higher compared to the 29% in the study of Jiang [31] and lower compared to the 45% in the study of Friedmann [10]. In a study on patients after coronary artery or valve surgery, Szekely [12] found that 42% of these patients presented clinically significant anxiety symptoms. These results stress the importance to screen for anxiety as well as for depression.…”
Section: Discussionmentioning
confidence: 93%
“…Both depression and anxiety relate to negative health outcomes such as recurrent cardiac events, impaired well being and quality of life and increased health care costs in these patient populations [8][9][10][11][12]. Early identification and accurate treatment are considered important in view of the patient's health and well being and from the perspective of cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent epidemiological studies have also showed a correlation between major depressive episodes and increased incidence of cardiovascular events both in a population of healthy subjects and in people with known cardiovascular disease [20][21][22][23][24]. However, growing bodies of studies have failed to detect this relation in patients with ischemic heart disease [25][26][27][28]. The conflicting results can be due to the usage of different depression scales for classifying participants as depressed.…”
Section: Emotional Disordersmentioning
confidence: 79%
“…Although anxiety and depression were positively and highly correlated in these patients, only anxiety was associated with increased mortality and morbidity. In addition trait anxiety was significantly higher in patients hospitalized with arrhythmia, congestive heart failure or myocardial infarction during a 4 year period after cardiac (CABG and valve) surgery [27]. In another study of our workgroup depression, anxiety, education, social isolation and mortality together were investigated 7.5 years after cardiac surgery.…”
Section: Anxiety and Cabgmentioning
confidence: 99%